First, let's simplify f(x):
f(x) = 2x + √(2x)
Now let's simplify g(x):
g(x) = √2 * x
To find (f⋅g)(x), we need to multiply f(x) and g(x).
(f⋅g)(x) = f(x) * g(x)
= (2x + √(2x)) * (√2 * x)
= (2x) * (√2 * x) + (√(2x) * √2 * x)
= 2√2 * x^2 + 2x^2
Now let's substitute x=2 into (f⋅g)(x):
(f⋅g)(2) = 2√2 * (2)^2 + 2(2)^2
= 2√2 * 4 + 2 * 4
= 8√2 + 8
Therefore, when x=2, (f⋅g)(x) is equal to 8√2 + 8.
If f(x)=2x=√+2x and g(x)=√2⋅x , evaluate (f⋅g)(x) when x=2 .
3 answers
is this correct?
Apologies for the mistake in my response. It looks like there was a confusion in the initial function f(x).
The corrected equation for f(x) should be:
f(x) = 2x + √(2x)
The equation for g(x) remains the same:
g(x) = √2 * x
Now let's evaluate (f⋅g)(x) when x = 2:
f(2) = 2(2) + √(2(2))
= 4 + √(4)
= 4 + 2
= 6
g(2) = √2 * 2
= 2√2
To find (f⋅g)(x), we multiply f(x) and g(x):
(f⋅g)(x) = f(x) * g(x)
= [2x + √(2x)] * [√2 * x]
= (2x * √2 * x) + (√(2x) * √2 * x)
= 2√2 * x^2 + 2x^2
Substituting x = 2 into (f⋅g)(x):
(f⋅g)(2) = 2√2 * (2)^2 + 2(2)^2
= 2√2 * 4 + 2 * 4
= 8√2 + 8
Therefore, when x = 2, the value of (f⋅g)(x) is 8√2 + 8.
The corrected equation for f(x) should be:
f(x) = 2x + √(2x)
The equation for g(x) remains the same:
g(x) = √2 * x
Now let's evaluate (f⋅g)(x) when x = 2:
f(2) = 2(2) + √(2(2))
= 4 + √(4)
= 4 + 2
= 6
g(2) = √2 * 2
= 2√2
To find (f⋅g)(x), we multiply f(x) and g(x):
(f⋅g)(x) = f(x) * g(x)
= [2x + √(2x)] * [√2 * x]
= (2x * √2 * x) + (√(2x) * √2 * x)
= 2√2 * x^2 + 2x^2
Substituting x = 2 into (f⋅g)(x):
(f⋅g)(2) = 2√2 * (2)^2 + 2(2)^2
= 2√2 * 4 + 2 * 4
= 8√2 + 8
Therefore, when x = 2, the value of (f⋅g)(x) is 8√2 + 8.